Radiation reaction studies in an all-optical set-up: experimental limitations. Issue 21 (30th November 2017) - Samarin, G. M.; Zepf, M.; Sarri, G.
Abstract : The recent development of ultra-high intensity laser facilities is finally opening up the possibility of studying high-field quantum electrodynamics in the laboratory. Arguably, one of the central phenomena in this area is that of quantum radiation reaction experienced by an ultra-relativistic electron beam as it propagates through the tight focus of a laser beam. In this paper, we discuss the major experimental challenges that are to be faced in order to extract meaningful and quantitative information from this class of experiments using existing and near-term laser facilities.